Testing the governance-performance relationship for the Tunisian banks: A GMM in system analysis - Nesrine Djebali; Khemais Zaghdoudi (Financial Innovation, 2020)
Rationale: This study aims to contribute to settling the lack of consensus regarding the determinants of bank performance, not only by considering bank governance, but also by including factors such as CEO compensation and risk management committee. Previous literature has included bank governance and considered only large banks in their surveys. The exclusion of other factors such as small- and medium-size banks may render the findings of these studies limited in applicability. Objective: The objective of this paper is to examine the impact of internal governance on bank performance. Methodology: To achieve this goal, we used annual data of a sample of ten Tunisian commercial banks listed in the Tunisian Stock Exchange observed during the period 1998-2015. We use the Generalized Method of Moments (GMM) to estimate the parameters of our econometric model. Results: Our study finds that the correlation between the size of the board of directors, the state's inclusion, and the presence of independent directors is positive and significant. On the other hand, we have found that CEO compensation, as well as foreign and institutional investors negatively affect the performance of the banks. Conclusions and implications: Tunisian banks are invited to broaden their size through appropriate restructuring, adopt new remuneration policies and define the optimal number of directors representing the state within the board of directors. Our results suggest managerial implications that can be of great value to ensuring the success of Tunisian banks. The latter should favor a higher presence of independent directors to reduce the bank control ineffectiveness caused by having a significant number of foreign and institutional investors in the board of directors.
Keywords: 650; Bank governance; Bank performance; Tunisian banks; GMM